Balancing Workload, Autonomy, and Coping Strategies: A Study of Private School Leadership in Nepal - Adhikari, Nab Raj; Amirrudin, Suraya; Khadka, Jiban (Journal of Business and Social Sciences Research, 2025)
The purpose of the study was to explore the extent and sources of occupational stress in private school principals in Kathmandu Valley, Nepal. It aims to explore the potential stressors or sources of stress in work life (i.e., heavy workload, conflicts with stakeholders, organisational changes, and limited resources) and their relationships with principals’ psychological well-being and job performance. A quantitative descriptive design was used to gather data from 245 principals through stratified random sampling and a structured questionnaire, which consisted of job demands, role clarity, co-worker support, and organisational change on a five-point Likert type scale. The descriptive statistics, Pearson correlation, and multiple regressions were used to examine the relationship between stress and demographic variables. Results indicated that 42% of principals reported high levels of stress, with the most prominent stressors being unreasonable workloads, low levels of support by colleagues, and unclear expectations of their role. Male principals and those with fewer years of managerial experience felt more stressed. The research emphasises the significance of developing autonomy in decision-making and support networks to reduce stress and to make principals happier and better at their jobs.